A construção das ilhas artificiais chinesas e a política de risco nas disputas territoriais do Sul do mar da China - Nascimento, Renally Késsia Paiva (2017)
In 2014, satellites from the Philippines identified construction of large artificial structures by China on seven reefs on the disputed Spratly Islands, in the south China sea. It was the beginning of what would be called reef-islandization or construction of artificial islands. These structures are being designed to meet civil demands and for military purposes. As for this latter utility of artificial constructions, China has promoted a vague discourse, which in turn has contributed to escalating suspicions and tensions, which has drawn the attention of the world to Southeast Asia. Given this scenario, this paper aims to understand if the artificial islands are a risk response of China to the regional security dynamics of Southeast Asia. Through this, three specific objectives will be presented: to investigate which antecedent factors had the causal force to make China adopt the policy of construction of the artificial islands; Understand the prospect theory and its main definitions, and the functionality of the model of political legitimation; Describe what these artificial constructions are and what their role in China's territorial politics. The research is based on a qualitative methodology whose line of elaboration will be developed through two tools: descriptive and explanatory-exploratory. In addition to this, bibliographic tools will be used. In short, the dissertation will be worked over three chapters: in the first chapter a review of the literature on territorial disputes and prospect theory; the second chapter will address the context of artificial constructions and how China perceives itself within these territorial disputes.. Based on the analysis of the need to avoid future losses, the third chapter will address how China's dissatisfaction with the status quo of the dispute in the South China Sea led the country to accept risk policies in order to Change the dynamics of this territorial game.